Factors that characterize the dispersion of sulfur dioxide in the Historic Center of Riobamba - Álvarez Luna, Silvio (2017)
Modeling of the dispersion of sulfur dioxide (SO2) in the historic center of Riobamba was done, because there is no similar to the projective investigation of the case; this, for a small town located in the Interandina Region, 2754 meters above sea level, which is projected gradually to the suburbs, by the chaotic central juncture. Because of the fleet and the conglomeration of public and educational institutions, which in turn concentrates lot of people in the sector in working hours, respiratory diseases would be generated by clinical data, probably caused by inhalation of so2 and other pollutants. Were performed at the same time, various technical monitoring to determine the prevalence of major pollutants in the environment; data were analyzed under the design scheme of main components to characterize trends correlation; and a mathematical dispersion model was established from the design described projective purposes.